Prepared for disaster: «Survivalism» and collapse in contemporary dystopia (the case of "The Walking Dead") - Rey Segovia, Ana Clara (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
The current economic and political crisis affects our daily life and also implies an individual crisis that calls into question both our inwards (subjectivity) and outwards expressions (of sociability, of inter-subjectivity). This exacerbates if we consider the highly likely «collapse» we will be facing according to the scientific consensus on environmental issues. By this we refer to a «zero point» that could precipitate a disaster of incalculable consequences. In this scenario, a considerable number of audiovisual and literary manifestations have assumed this collapse as an important element of their plots. The analysis of the TV show The Walking Dead allows me to address a possible representation of a future post-collapse society, in the context of the so called «survivalist» or «prepper» movements of the United States of America. The characteristics of these groups reflect the permanent crisis of the contemporary subject, who needs to anticipate future in order to feel safe.
Keywords: dystopia; collapse; survivalism; preppers; crisis; subjectivity